1997
DOI: 10.3758/bf03211303
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing chairs and naming pears: Category differences in object processing as a function of task and priming

Abstract: Four experiments are reported examining the locus of structural similarity effects in picture recognition and naming with normal subjects. Subjects carried out superordinate categorization and naming tasks with picture and word forms of clothing, furniture, fruit, and vegetable exemplars. The main findings were as follows: (1) Responses to pictures of fruit and vegetables ("structurally similar" objects) were slowed relative to pictures of clothing and furniture ("structurally dissimilar" objects). This struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 67 publications
6
46
0
Order By: Relevance
“…Lloyd-Jones and Humphreys (1997aHumphreys ( , 1997b have suggested that neurologicalimpairments may exacerbate previously existing normal processing differences. We present a similar case here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lloyd-Jones and Humphreys (1997aHumphreys ( , 1997b have suggested that neurologicalimpairments may exacerbate previously existing normal processing differences. We present a similar case here.…”
Section: Resultsmentioning
confidence: 99%
“…Local parts take longer to be processed than more global aspects of shape such as outline contour (e.g., Eriksen, O'Hara, & Eriksen, 1982;Hughes, Nozawa, & Kitterle, 1996;Kimchi, 1992;Lupker, 1979;Navon, 1977;Sanocki,1993;Townsend, Hu, & Kadlec, 1988;Watt, 1988). It follows that a processing difficulty for living things will be more evident in tasks where local features are fully processed, such as semantic categorization and naming with unlimited exposure durations (Lloyd-Jones & Humphreys, 1997a, 1997b than in tasks where this may not be the case, such as naming at short exposure durations (e.g., Humphreys et al, 1995) and object decision (Lloyd-Jones & Humphreys, 1997b). In contrast, with short exposure durations, a processing difficulty for nonliving things emerges because performance is based primarily on global aspects of shape and, in particular, the low diagnosticity of outline contour for recognition of nonliving things relative to living things increases processing time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy participants, visual identification is influenced by visual similarity: Items that come from visually dissimilar categories are identified faster than items that come from visually similar categories (Dickerson & Humphreys, 1999;Humphreys, Riddoch, & Quinlan, 1988;Lloyd-Jones & Humphreys, 1997a, 1997b. Visual similarity also impacts the identification performance of patients with visual agnosia.…”
Section: Visual Similarity Influences Visual Identificationmentioning
confidence: 99%
“…Although the two tasks share many of the same component processes, they also differ in ways that may potentially affect language selection. For example, in picture naming, the process of identifying the pictured object is thought to require the computation of a structural description that is likely to share depicted features with other objects drawn from the same semantic category (e.g., Lloyd-Jones & Humphreys, 1997). In translation, the presented word also has to be identified, but the processes that contribute to word recognition are likely to involve the activation of word neighbors that share lexical, rather than visual/semantic, features with the target.…”
Section: Stroop Effects In Bilingual Translation Natasha a Miller Anmentioning
confidence: 99%